An Evaluation of Complications of Ultrasound Guided Percutaneous Nephrostomy in Cases of Obstructive Uropathy - Muhammad Saddiq Haris, Abdur Rasheed, Syed Atif Hussain, Farhat Islam, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the complications of ultrasound guided percutaneous nephrostomy in cases of obstructive uropathy at tertiary care hospital. Study design: Case series Duration of study: From February 2022 to August 2022. Setting: Department of Urology, Sheikh Zaid Hospital, Rahim Yar Khan. Material and methods: Total 133 patients having age between 20-40 years either gender with obstructive uropathy due to ureteric obstruction caused by (impacted ureteric stones, PUJ obstruction, carcinoma prostate involving ureters, iatrogenic ureteric injury and bladder tumors) were included in the study and post procedure complications were evaluated. Results: Mean age was 44.83 ± 13.05 years. Regarding presenting symptoms, total 94 (71%) patients had decreased urine amount, 29 (22%) patients had flank pain while 10 (7%) patients had fever. Septicemia was found in 11 (8.33%) patients, bleeding in 4 (3%) patients followed by PCN dislodgement in 8 (6%) patients. Conclusion: Results of this study revealed that septicemia was the most common complication in cases of obstructive uropathy after PCN. More than 50% patients were between 41-60 years. Male population was commonly suffered from obstructive uropathy. Most of the patients had bilateral obstructive uropathy and decreased urine output was common presenting symptom. Keywords: PCN, obstructive uropathy, nephrostomy, bleeding, blockage